2018
DOI: 10.1021/acs.est.7b06387
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Chemistry

Abstract: This review aims to encapsulate the importance, ubiquity, and complexity of indoor chemistry. We discuss the many sources of indoor air pollutants and summarize their chemical reactions in the air and on surfaces. We also summarize some of the known impacts of human occupants, who act as sources and sinks of indoor chemicals, and whose activities (e.g., cooking, cleaning, smoking) can lead to extremely high pollutant concentrations. As we begin to use increasingly sensitive and selective instrumentation indoor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
232
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 220 publications
(233 citation statements)
references
References 123 publications
1
232
0
Order By: Relevance
“…Equation (1) Equations (3)(4)(5)(6)(7)(8), k shirt , the first-order ozone removal rate coefficient by the t-shirts, was calculated as k shirt = k sur − k chamber = (1.2 ± 0.1) h −1 .…”
Section: Ozonementioning
confidence: 99%
See 2 more Smart Citations
“…Equation (1) Equations (3)(4)(5)(6)(7)(8), k shirt , the first-order ozone removal rate coefficient by the t-shirts, was calculated as k shirt = k sur − k chamber = (1.2 ± 0.1) h −1 .…”
Section: Ozonementioning
confidence: 99%
“…[1][2][3][4] Building materials, furnishings and carpeting, cleaning products, personal care products, human activities, as well as outdoor air have been considered major sources of indoor air pollutants. [1][2][3][4] Building materials, furnishings and carpeting, cleaning products, personal care products, human activities, as well as outdoor air have been considered major sources of indoor air pollutants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower levels of VOCs in summer might be due to photochemical reactions, which are more effective with higher radiation of the summer, resulting in VOCs removal . Weschler and Carslaw have shown that light can propagate through indoor environments with some attenuation, both through the use of indoor lighting and through windows. Consequently, photochemical processes, and especially those reactions that require less energy such as the photolysis of aldehydes, also occur indoors although more slowly than outdoors.…”
Section: Resultsmentioning
confidence: 99%
“…I/O ratios for the main detected compounds were <1 (Figure ). Thus, in the indoor pool, the major sources of studied VOCs were the outdoor sources and probably, the indoor photochemical transformations of these compounds by the solar light penetrating through the windows; but not being generated from the organic compounds derived of disinfection by‐products present in the indoor air. One prior study included analysis of VOCs in indoor swimming pools; however, different individual VOCs were not measured, but rather the sum of all of them (TVOCs) was reported.…”
Section: Resultsmentioning
confidence: 99%